Perancangan dan Implementasi Media Kartu Kuartet pada Pembelajaran Pendidikan Pancasila Siswa Kelas IV Sekolah Dasar Wilayah 3T - Abadi, Candres; Trisnayanti, Yetty (JOEAI (Journal of Education and Instruction), 2025)
This study aims to develop a product in the form of quartet cards for Pancasila Education learning, in accordance with the curriculum, and to produce valid, practical, and potentially effective quartet cards. This research used research and development (R&D) with the ADDIE model. The results indicate that the quality of the quartet cards, in terms of validity, is categorized as valid, with an Aiken coefficient of 0.780 for language experts, 0.85 for material experts, and 0.81 for media experts, categorizing them as very valid. Furthermore, the analysis of teacher and student practicality assessment sheets for the quartet cards met the criteria for practicality with an average score of 86.31% and effectiveness with an average score of 0.71. The conclusion is that the quartet cards in Pancasila Education learning meet the criteria for validity, practicality, and potential effectiveness, and can therefore be used in learning activities. Keywords: Pancasila Education, Quartet Cards, Elementary Schools, 3T Regions